1996
DOI: 10.1016/0014-5793(96)00841-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and refolding of recombinant Haemophilus influenzae type b porin produced in Bacillus subtilis

Abstract: The major diffusion channel in the outer membrane ofHaemophilus influenzae type b (l-lib) is porin (341 amino acids; Mr 37 782). The Hib porin gene was cloned and overexpressed in Bacillus subtilis. Recombinant Hib porin (Bac porin), having aggregated into inclusion bodies, was purified under denaturing conditions and subsequently refolded. To compare Bac porin that is intrinsically devoid of lipooligosaccharides versus native Hib porin, the properties of Bac porin were assessed by the following four criteria:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Although we do not know the relative orientation of the reconstituted OEP75, our data indicate that reconstitution leads to a highly preferential orientation of the protein in the liposome membrane. Similar observations on the functional reconstitution of membrane channels from denatured proteins have been made during reconstitution studies using heterologously expressed Haemophilus influenzae porin (Dahan et al, 1996), E.coli OmpA and OmpF (Surrey and Jähnig, 1992;Surrey et al, 1996), porin from Rhodopseudomonas blastica (Schmidt et al, 1996) or the SecY, SecE protein translocase (Brundage et al, 1990;Akimaru et al, 1991;Driessen, 1992). Unidirectional orientation and membrane insertion has also been observed previously (Surrey and Jähnig, 1992;Dahan et al, 1996;Surrey et al, 1996).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although we do not know the relative orientation of the reconstituted OEP75, our data indicate that reconstitution leads to a highly preferential orientation of the protein in the liposome membrane. Similar observations on the functional reconstitution of membrane channels from denatured proteins have been made during reconstitution studies using heterologously expressed Haemophilus influenzae porin (Dahan et al, 1996), E.coli OmpA and OmpF (Surrey and Jähnig, 1992;Surrey et al, 1996), porin from Rhodopseudomonas blastica (Schmidt et al, 1996) or the SecY, SecE protein translocase (Brundage et al, 1990;Akimaru et al, 1991;Driessen, 1992). Unidirectional orientation and membrane insertion has also been observed previously (Surrey and Jähnig, 1992;Dahan et al, 1996;Surrey et al, 1996).…”
Section: Discussionsupporting
confidence: 80%
“…Similar observations on the functional reconstitution of membrane channels from denatured proteins have been made during reconstitution studies using heterologously expressed Haemophilus influenzae porin (Dahan et al ., 1996), E.coli OmpA and OmpF (Surrey and Jähnig, 1992; Surrey et al ., 1996), porin from Rhodopseudomonas blastica (Schmidt et al ., 1996) or the SecY, SecE protein translocase (Brundage et al ., 1990; Akimaru et al ., 1991; Driessen, 1992). Unidirectional orientation and membrane insertion has also been observed previously (Surrey and Jähnig, 1992; Dahan et al ., 1996; Surrey et al ., 1996). It is worth noting that we applied a reconstitution protocol similar to that of Surrey and Jähnig (1992), specifically without using detergents for the protein solubilization.…”
Section: Discussionsupporting
confidence: 73%
“…However, a few studies have reported expression of porins lacking signal peptide sequences as aggregated inclusion bodies. Examples are the expression of Hib (Haemophilus influenzae type b) in Bacillus subtilis using pKTH288 [36], Neisseria species class 3 porin in E. coli BL21(DE3) ompA using pET17b [26], Rhodopseudomonas blastica porin in E. coli BL21(DE3)pLysS using pET3a [37], Burkholderia cepacia OpcP in E. coli JM109 using pTrc99A [38], Orientia tsutsugamushi r56 in E. coli BL21 using pET11a [39] and Mycobacterium smegmatis MspA in E. coli BL21(DE3) using pET24(+) [40]. In the present study, BpsOmp38 and BthOmp38 lacking signal peptide sequences were expressed successfully as insoluble inclusion bodies in E. coli Origami(DE3) using the pET23d(+) vector system.…”
Section: Discussionmentioning
confidence: 99%
“…CD spectra were recorded at room temperature on a Jasco J-600 spectropolarimeter. Samples containing 0.4 mg´mL 21 OmpT in buffer B were analyzed using quartz cells with a path length of 0.2 mm.…”
Section: Methodsmentioning
confidence: 99%